Mexican American Adults in Higher Education: A Qualitative Study - Janet Ann DeRosa (Adult Education Research Conference, 2014)
This study explored the experiences of Mexican Americans who completed a bachelor degree as adult learners. With the primary focus on Mexican Americans’ bicultural experiences, the study’s findings point to the significance of the process in becoming bicultural and how that process influences college degree attainment.